2002
DOI: 10.1097/00042737-200204000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Doppler measurements: a surrogate marker of liver fibrosis?

Abstract: Doppler measurements of the portal vein, hepatic artery and hepatic vein(s) are not a valid surrogate marker of liver fibrosis. Nor are Doppler measurements a useful method to estimate the degree of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 20 publications
0
53
0
4
Order By: Relevance
“…Published data on Doppler US methods used in liver fibrosis differ, and thus the clinical usefulness of Doppler flow measurements for the diagnosis of hepatic fibrosis remains controversial. 13,31,32 Quantitative measures include portal vein blood volume, mean or maximum portal vein velocity, portal blood flow, congestion index of the portal vein, effective portal liver perfusion, and resistance indices of the liver and the spleen 33,34 (Figure 2), including our results compared to the results of the previous investigators in the field. Additionally, pulse wave Doppler can be applied to obtain waveforms (phasicity) of the portal vein and hepatic vein.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Published data on Doppler US methods used in liver fibrosis differ, and thus the clinical usefulness of Doppler flow measurements for the diagnosis of hepatic fibrosis remains controversial. 13,31,32 Quantitative measures include portal vein blood volume, mean or maximum portal vein velocity, portal blood flow, congestion index of the portal vein, effective portal liver perfusion, and resistance indices of the liver and the spleen 33,34 (Figure 2), including our results compared to the results of the previous investigators in the field. Additionally, pulse wave Doppler can be applied to obtain waveforms (phasicity) of the portal vein and hepatic vein.…”
Section: Discussionmentioning
confidence: 85%
“…Liver blood flow undergoes complex changes with the progression of chronic liver disease, which should be detected with dopplerographic examinations. Characteristic features of liver cirrhosis are decreasing portal bloodflow velocity, disappearance of pulsatility, change in flow detection in the portal vein from hepatopetal to hepatofugal in more severe cases, [10][11][12][13][14] and increase of resistive index in the hepatic artery. [15][16][17] The most characteristic dopplerographic sign has been suggested: changes in hepatic vein Doppler curve waveform from triphasic to biphasic and monophasic.…”
mentioning
confidence: 99%
“…Bernatik et al [37] reported that V MAX and V TAM velocities are reduced at end-stage fibrosis, while DPI does not change significantly and progression of liver fibrosis is associated with a continuous increase in HA resistive index (RI), suggesting that Doppler parameters are not useful in assessing the stage of liver fibrosis. In our study, although the mean HA RI value was significantly increased (P = 0.013) in CIR group compared to CVH group, it was not affected in CVH patients at different fibrosis stages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, positive correlation studies have usually referred to the velocity ratio of hepatic www.wjgnet.com artery to portal vein or the resistive index in hepatic artery. However, the role of CDU remains controversial regarding the reproducibility [33][34][35][36] and the statistical significance [37,38] of the measurements in hepatic fibrosis and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ancak biyopsi invaziv bir işlemdir ve komplikasyon riski mevcuttur. Ayrıca bazı hastalarda yalancı sonuç verebilmektedir (3). Bu nedenler, karaciğer fibrozis evresinin takibinde biyopsinin rutin kullanımını kısıtlamaktadır.…”
Section: Introductionunclassified